2006
DOI: 10.1007/11687238_41
|View full text |Cite
|
Sign up to set email alerts
|

On Exploring the Power-Law Relationship in the Itemset Support Distribution

Abstract: Abstract. We identify and explore in this paper an important phenomenon that the power-law relationship appears in the distribution of itemset supports. Characterizing such a relationship will benefit many applications such as providing the direction of tuning the performance of the frequent-itemset mining. Nevertheless, due to the explosive number of itemsets, it will be prohibitively expensive to retrieve characteristics of the power-law relationship in the distribution of itemset supports. As such, we also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Two recent papers [3,4] used empirical studies on various retail transaction datasets to demonstrate that power-law relationships exist in the pattern support distributions of real datasets. It is suggested that this is caused by self-similarity within the pattern support distribution.…”
Section: Power-law Relationships In Psdsmentioning
confidence: 99%
“…Two recent papers [3,4] used empirical studies on various retail transaction datasets to demonstrate that power-law relationships exist in the pattern support distributions of real datasets. It is suggested that this is caused by self-similarity within the pattern support distribution.…”
Section: Power-law Relationships In Psdsmentioning
confidence: 99%